Life cycle assessment of solid waste management options: A Review - Yadav, Pooja; Samadder, S R (Recent Research in Science and Technology, 2014)
<!--[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]--> Evaluating the environmental performance of municipal solid waste management options is a complex job. LCA is an analytical tool (software) for assessing the environmental acceptability of municipal solid waste management (MSWM) options. LCA is currently being used in several countries to evaluate different strategies for integrated solid waste management and to evaluate treatment options for waste fractions. According to the characteristics of solid wastes, and availability of disposal options, LCA helps in supporting the identification of opportunities for pollution prevention and reductions in resource consumption while taking the entire solid waste life cycle. The primary elements of solid waste management are generation, collection, transportation, treatment, and disposal. Different scenarios were developed and reported as alternatives to the current waste management systems. The most prominent is material recovery facility (MRF) and other methods involve source reduction, reuse, recycling, composting, incineration, energy recovery, on-site burial, open burning and bioremediation. The goal of this review is to determine the most environmentally friendly option of MSWM system with the help of LCA. <!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]-->